2011
DOI: 10.22605/rrh1515
|View full text |Cite
|
Sign up to set email alerts
|

Attraction and retention of qualified health workers to rural areas in Nigeria: a case study of four LGAs in Ogun State, Nigeria

Abstract: Introduction: A shortage of health workers is a major problem for Nigeria, especially in rural areas where more than 70% of the population live. At the primary care level, trained community health officers provide services normally reserved for doctors or medical specialists. The community health officers must therefore be supported and motivated to provide effective quality healthcare services. This study aimed to determine factors that will attract and retain rural and urban health workers to rural Nigerian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Although provision of accommodation has been identified as retention strategy for PHC workers in Nigeria,2 especially in rural areas,53 we found that, for both employed and volunteer CHWs, basic accommodation provision within the community of practice was inversely related to motivation for service delivery. This finding also contradicts studies which identify provision of housing or housing allowances as incentives to work in rural or remote areas 20 25.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although provision of accommodation has been identified as retention strategy for PHC workers in Nigeria,2 especially in rural areas,53 we found that, for both employed and volunteer CHWs, basic accommodation provision within the community of practice was inversely related to motivation for service delivery. This finding also contradicts studies which identify provision of housing or housing allowances as incentives to work in rural or remote areas 20 25.…”
Section: Discussionmentioning
confidence: 62%
“…There is insufficient evidence to inform this issue of subspecialisation; however, the findings from our study suggest that this is an important area for further research. 52 Although provision of accommodation has been identified as retention strategy for PHC workers in Nigeria, 2 especially in rural areas, 53 we found that, for both employed and volunteer CHWs, basic accommodation provision within the community of practice was inversely related to motivation for service delivery. This finding also contradicts studies which identify provision of housing or housing allowances as incentives to…”
Section: Discussionmentioning
confidence: 67%
“…In another Nigerian study by Ebuehi and Campbell, a better living environment and family support systems were reported to motivate the health workers to stay in rural areas. 32 From the findings of this study, we argue that it is the relationship between the health workers and the local communities that can enhance the retention of health workers. We further argue that the local community leaders have a large role in linking and integrating the health workers with the local communities and thus can foster good relationships, contributing to the retention of health workers.…”
Section: Actions Of the Local Community And Retention Of Health Workersmentioning
confidence: 77%
“…Ebuehi et al in their study stated that easy access to equipment and supplies improves the retention of healthcare workers in rural areas. 35 Another study has pointed out that less attention is paid to rural services, so the facilities and equipment of rural centres are not of good quantity and quality and do not meet the peak time needs of doctors' visits. 25 The high workload in disadvantaged areas greatly affects the tendency of dentists to stay in those areas.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate disposable materials and equipment are effective on creating favourable working conditions and retaining dentists in deprived areas. Ebuehi et al in their study stated that easy access to equipment and supplies improves the retention of healthcare workers in rural areas 35 . Another study has pointed out that less attention is paid to rural services, so the facilities and equipment of rural centres are not of good quantity and quality and do not meet the peak time needs of doctors' visits 25 …”
Section: Discussionmentioning
confidence: 99%